Determinants of cesarean mode of childbirth among Rwandan women of childbearing age: Evidence from the 2019-2020 Rwanda Demographic and Health Survey (RDHS) - Nsereko Etienne; Uwase Aline; Mpinganzima Ornella; Usanzineza Henriette; Niyitegeka Jean Pierre; Turabayo Jean Léonard; Mwiseneza Marie Josee; Mugeni Girimpundu Candide; Moreland Patricia (Wiley, 2024)
Abstract Background Rwanda has made progress in reducing maternal mortality, with rates decreasing by three‐quarters between 1990 and 2015, in part due to increased access to cesarean delivery (CD). However, the prevalence of CD is also increasing for reasons other than clinical indications. Rwanda's 15% CD delivery rate is higher than World Health Organization guidelines, sparking debate about optimal CD use and potential negative outcomes in child and maternal health. This study aimed to identify the key clinical and nonclinical factors relating to CD in Rwanda. Methods A secondary data analysis of the Rwanda Demographic and Health Survey (2019-2020) was performed, using the outcome variable of vaginal birth versus CD in women who had delivered in the survey period and for 5 years preceding. We used logistic regression modeling to identify the explanatory sociodemographic, economic, and obstetric characteristics associated with CD. Results More than half of participants were between 20‐ and 34‐year old, 65.2% had completed primary school at least, 79.0% lived in rural areas, and 81.2% had health insurance. Fifteen percent of participants had given birth by CD in the preceding 5 years. CD was independently associated with higher levels of education, religion, higher socioeconomic status, perceived financial constraints, and giving birth in a private health facility. Obstetric predictors for CD included twin pregnancy, male infancy, and primiparity. Conclusion Results suggest that indications for CD should be monitored and the birthing preferences of women further evaluated, with guidelines implemented to inform decision‐making around CD.